2017
DOI: 10.1111/ppl.12656
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of enhancing vacuolar K/H exchange in tomato

Abstract: Cation antiporters of the NHX family are widely regarded as determinants of salt tolerance due to their capacity to drive sodium (Na) and sequester it into vacuoles. Recent work shows, however, that NHX transporters are primarily involved in vacuolar potassium (K) storage. Over-expression of the K/H antiporter AtNHX1 in tomato increases K accumulation into vacuoles and plant sensitivity to K deprivation. Here we show that the appearance of early leaf symptoms of K deficiency was associated with higher concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(115 reference statements)
0
9
0
1
Order By: Relevance
“…An informative work showed that overexpression of the AtNHX1 in tomato induced K + -deficiency symptoms despite transgenic plants having greater K + contents than controls (Leidi et al., 2010). The intense sequestration of K + in NHX1-overexpressing plants reduced cytosolic K + activity, primed the induction of the high-affinity K + uptake system, and elicited an array of metabolic and hormonal disorders related to K + deprivation (Leidi et al., 2010; De Luca et al., 2018). Notwithstanding these unintended effects resulting from NHX overexpression, NHX proteins do increase salt tolerance, presumably because retention of cellular K + is a requisite for adaptation to a saline environment (Jiang et al., 2010).…”
Section: Compartmentation and Storage Into Vacuolesmentioning
confidence: 99%
“…An informative work showed that overexpression of the AtNHX1 in tomato induced K + -deficiency symptoms despite transgenic plants having greater K + contents than controls (Leidi et al., 2010). The intense sequestration of K + in NHX1-overexpressing plants reduced cytosolic K + activity, primed the induction of the high-affinity K + uptake system, and elicited an array of metabolic and hormonal disorders related to K + deprivation (Leidi et al., 2010; De Luca et al., 2018). Notwithstanding these unintended effects resulting from NHX overexpression, NHX proteins do increase salt tolerance, presumably because retention of cellular K + is a requisite for adaptation to a saline environment (Jiang et al., 2010).…”
Section: Compartmentation and Storage Into Vacuolesmentioning
confidence: 99%
“…The result suggests that the TRV:GhNHX4A plants accumulate Na + in the stem, but not K + in the roots, in response to salt stress. The overexpression of AtNHX1 in A. thaliana increases the resistance of the transgenic plants to Na + and induces the absorption of K + [ 16 , 66 , 67 ]. Similarly, AtNHX1 -overexpressing wheat plants treated with 100–150 mM NaCl have lower Na + concentrations and higher K + concentrations than wild-type lines [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…An informative work showed that overexpression of the AtNHX1 in tomato induced K + -de iciency symptoms despite transgenic plants having greater K + contents than controls [72]. The intense sequestration of K + in NHX1-overexpressing plants reduced cytosolic K + activity, primed the induction of the highaf inity K + uptake system, and elicited an array of metabolic and hormonal disorders related to K + deprivation [72,118]. Notwithstanding these unintended effects resulting from NHX overexpression, NHX proteins do increase salt tolerance, presumably because retention of cellular K + is a requisite for adaptation to a saline environment [119].…”
Section: Cation-proton Antiporters (Cpa)mentioning
confidence: 99%